Transport usage among students at the Universiti Teknologi Malaysia campus [electronic resource] - Ain Zubaidah Mohd. Sabri, 1989-; Mohd. Badruddin Mohd. Yusof (2012)
Project Paper (Sarjana Muda Kejuruteraan (Awam)) - Universiti Teknologi Malaysia, 2012